2006
DOI: 10.1016/j.seizure.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of subjective complaints in patients with epilepsy who seem to be well-controlled with anti-epileptic drugs

Abstract: Patients who were considered to be well-controlled proved to report an unexpectedly high number of subjective complaints. Both medication and aspects of personality contributed to the level of complaints. Our study illustrates that subjective side-effects are easily overlooked in everyday clinical practice, possibly because in practice a generally phrased question is used to detect side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 12 publications
3
58
2
2
Order By: Relevance
“…The side effects of AED treatment questionnaire (SIDAED) [2], developed by our group, was used as the basis for the questionnaire. The original 10 side-effect categories of the SIDAED were compressed into four categories in order to focus on the most commonly reported side-effects.…”
Section: Questionnairementioning
confidence: 99%
See 3 more Smart Citations
“…The side effects of AED treatment questionnaire (SIDAED) [2], developed by our group, was used as the basis for the questionnaire. The original 10 side-effect categories of the SIDAED were compressed into four categories in order to focus on the most commonly reported side-effects.…”
Section: Questionnairementioning
confidence: 99%
“…Mood and behavioral complaints such as agitation or irritability and depression are reported less frequently (22%). Another study reported a prevalence of 67% of moderate to severe subjective complaints of patients who were considered to be wellcontrolled (defined as unchanged medication for the last six months) [2]. Cognitive complaints were reported most frequently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neste contexto, quanto maior o tempo livre de crises epilépticas, melhor será o desenvolvimento do córtex (Baglietto et al, 2001;Jeong et al, 2011;Metz-Lutz et al, 2011;Northcott et al, 2005;Piccirilli et al, 1988) e o desempenho de suas funções sem interferências, assim como o aprendizado de estratégias para aprimorar seu desempenho (Aldenkamp, Baker, & Meador, 2004;Hermann et al, 2010Hermann & Seidenberg, 1995;Hermann et al, 2006 (Uijl et al, 2006;Lagae, 2006). Ao diminuírem a excitabilidade neuronal e, consequentemente, as crises epilépticas, afetam os mecanismos excitatórios do neurônio e podem prejudicar a cognição (Meador, 2006).…”
Section: Impacto Das Variáveis Clínicas Da Epilepsia No Funcionamentounclassified